X-ray line spectrometry in experiments with the aluminium Z-pinch - Anan’ev, S.S.; Dan’ko, S.A.; Kalinin, Yu.G.; Ye Fan; Qin Yi; Jiang Shuqing; Xue Feibiao; Li Zhenghong; Yang Jianlun; Xu Rongkun (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
X-ray line spectrometry with temporal resolution was developed for registration of [He]- and [H]-like aluminium ions spectrum. It was chosen a scheme with scintillator converting X-ray spectrum into the visible image, which was transferred through the flexible optical fiber to the entrance slit of the streak camera. In Z-pinch experiment on the high current S-300 generator the aluminium line spectrum was registered with nanosecond time resolution. The simultaneous appearance of [He]- and [H]-like aluminium ions radiation was observed, that is the evidence of high electron temperature existence in the plasma for a long time before the main part of the load mass comes to the axis. The noticeably changing of radiating plasma parameters was found after the computer treatment of line spectra: the electron concentration is varied in five times ((3…14)×10^19 cm^-3), electron temperature in three times (0.3…1 keV), ion temperature in five times (20…100 keV), – during 50 ns. The great difference between the electron and ion temperature holds during all radiation time and demonstrates the ineffective energy transfer from the kinetic energy of ions to electron. Разработана методика для регистрации с временным разрешением рентгеновских линий [He]- и [H]-подобных ионов алюминия. Рентгеновский спектр преобразовывался с помощью сцинтиллятора в видимое изображение, которое переносилось гибким световодом на входную щель электронно-оптического преобразователя. Регистрация спектра проводилась с наносекундным разрешением в экспериментах с Z-пинчем на сильноточном генераторе С-300. Наблюдалось одновременное появление линий [He]- и [H]-подобных ионов алюминия, что является свидетельством наличия высокой электронной температуры в плазме задолго до момента прихода к оси основной массы Z-пинча. Компьютерная обработка спектров выявила значительные изменения параметров плазмы в процессе сжатия: концентрации в пять раз ((3…14)×10^19 см^-3), электронной температуры в три (0.3…1 кэВ), ионной температуры в пять раз (20…100 кэВ) – за 50 нс. Большой разрыв между ионной и электронной температурами демонстрирует неэффективность передачи энергии от ионов к электронам. Розроблено методику для реєстрації з часовим дозволом рентгенівських ліній [He]- і [H]-подібних іонів алюмінію. Рентгенівський спектр перетворювався за допомогою сцинтиллятора у видиме зображення, що переносилося гнучким світловодом на вхідну щілину електронно-оптичного перетворювача. Реєстрація спектра проводилася з наносекундним дозволом в експериментах з Z-пінчем на потужнострумовому генераторі С-300. Спостерігалася одночасна поява ліній [He]- і [H]-подібних іонів алюмінію, що є свідченням наявності високої електронної температури в плазмі задовго до моменту приходу до осі основної маси Z-пінча. Комп'ютерна обробка спектрів виявила значні зміни параметрів плазми в процесі стиску: концентрації в п'ять разів ((3...14)×10^19см^-3), електронної температури в три (0.3...1кеВ), іонної температури в п'ять разів (20...100 кеВ) – за 50 нс. Великий розрив між іонною й електронною температурами демонструє неефективність передачі енергії від іонів до електронів.